Online Purchase Intention: A Study Among Gen X in Malaysia - Anushia Chelvarayan; Lim Fu Hao; Yeo Sook Fern; Hazlaili Hashim (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
In recent years, changes in the commercial sector, combined with the increasing popularity of the Internet, have made Malaysian businesses increasingly conscious of the relevance of E-business in establishing a competitive edge in the worldwide market. As a result, knowing the elements that drive online purchase intention could help marketers create more effective marketing techniques for specific categories. Trust, product and service quality, customer satisfaction, and delivery speed are the four characteristics that influence online purchase intention in this study. According to 203 Generation X respondents, three characteristics had a significant impact on online purchase intention. The only exception was the product and service quality. The data and information acquired in this study will aid researchers, online platform developers, financial institutions, marketers, and the government because we will be able to examine and understand the elements that encourage Gen X in Malaysia to purchase online.